Formulation and Antioxidant Activity Test Of Body Lotion Preparation of Ethanol Extract of Sky Mustard Leaves (Cyanthillium cinereum (L) H.Rob) As A Moisturizer - Ika Julianti Tambunan; Siti Muliani (Jurnal FARMASIMED (JFM), 2025)
The skin is the first protection to ward off free radicals. Cosmetics used on the skin throughout the body are body lotions. The content of the sky mustard leaves (Cyanthillium cinereum (L) H. Rob) are alkaloid compounds, phenols, saponins, steroids, tannins, and flavonoids that function as antioxidants. This study aims to determine the antioxidant activity of the formulation of body lotion preparations of ethanol extract of sky mustard leaves. This study was conducted using an experimental method. The method of maceration of sky mustard leaves (Cyanthillium cinereum (L) H. Rob) using 96% ethanol. The methods used include selecting a standard formula, making body lotion preparations in concentrations of 1%, 1.5%, 2% and blanks, as well as evaluating the physical quality of the preparations and testing antioxidant activity using the DPPH method. The results showed that the leaves of the sky mustard (Cyanthillium cinereum (L) H. Rob) can be formulated into a body lotion preparation. The preparation obtained was stable and homogeneous, an oil-in-water emulsion type, pH immediately after being made 5.6 - 6.0 and after the cycling test 6.0 - 6.05, with a viscosity value of 2,300-4750 mPa's. The body lotion preparation of the sky mustard leaves with a concentration of 2% was the best preparation with a recovery percentage of 57.53% and an IC50 value of 61.38 ppm, including the "strong" category. The extract of the sky mustard leaves had an IC50 value of 14.75 ppm, which was categorized as "very strong". The blank preparation had an IC50 value of 156.91 ppm, including the "moderate" category.